EcoMat functional materials for green energy and environment. (John Wiley & Sons, Inc., Wiley Beijing Office, 2019)
"EcoMat aims to publish on a wide variety of topics from different disciplines that share the focus on cutting-edge advanced materials for green energy and environment. The scope of EcoMat is intentionally broad and encompasses relevant fields for developing ecofriendly and sustainable energy, including topics such as wind, water and solar energy harvesting & conversion, batteries and supercapacitors, energy system and networks, thermoelectrics, fuel cells, carbon capture and storage, piezo and triboelectrics, water and air pollution control & cleaning, artificial photosynthesis, hydrogen generation & storage. This journal recognises the complexity of issues, and therefore particularly welcomes innovative interdisciplinary researches with wide impact. It will aim to make a mark in the materials science and adjacent fields with ambitions of a high academic impact."--Publisher.